Attitudes of Experienced Seafarers as Predictor of ISM Code Implementation: A Croatian Example - Mišković, Darijo; Jelaska, Igor; Ivče, Renato (Promet - Traffic&Transportation, 2019)
The aim of this paper is to identify what attitudes towards safety performance indicators influence the attitudes towards successfulness of ISM Code implementation among contemporary seafarers. Secondly, the goal of the research was to obtain insight into the seafarer’s attitudes towards the current state of ISM implementation and safety performance. Consequently, a sample of N=330 seafarers was examined regarding their attitudes towards safety performance variables and ISM Code implementation. By using multiple regression analysis it was concluded that well designed and structured safety rules and procedures, positive work environment and adequate communication can make significant contributions to seafarers’ attitudes towards ISM implementation.